Widespread signatures of recent selection linked to nucleosome positioning in the human lineage - Prendergast, James G.D.; Semple, Colin A.M.

(untitled) (Genome Research, 2011)
In this study we investigated the strengths and modes of selection associated with nucleosome positioning in the human lineage through the comparison of interspecies and intraspecies rates of divergence. We identify significant evidence for both positive and negative selection linked to human nucleosome positioning for the first time, implicating a widespread and important role for DNA sequence in the location of well-positioned nucleosomes. Selection appears to be acting on particular base substitutions to maintain optimum GC compositions in core and linker regions, with, e.g., unexpectedly elevated rates of C→T substitutions during recent human evolution at linker regions 60–90 bp from the nucleosome dyad but significant depletion of the same substitutions within nucleosome core regions. These patterns are strikingly consistent with the known relationships between genomic sequence composition and nucleosome assembly. By stratifying nucleosomes according to the GC content of their genomic neighborhood, we also show that the strength and direction of selection detected is dictated by local GC content. Intriguingly these signatures of selection are not restricted to nucleosomes in close proximity to exons, suggesting the correct positioning of nucleosomes is not only important in and around coding regions. This analysis provides strong evidence that the genomic sequences associated with nucleosomes are not evolving neutrally, and suggests that underlying DNA sequence is an important factor in nucleosome positioning. Recent signatures of selection linked to genomic features as ubiquitous as the nucleosome have important implications for human genome evolution and disease.